2018
DOI: 10.1590/2446-4740.180040
|View full text |Cite
|
Sign up to set email alerts
|

The temporal stability of recurrence quantification analysis attributes from chronic atrial fibrillation electrograms

Abstract: The temporal behavior of atrial electrograms (AEGs) collected during persistent atrial fibrillation (persAF) directly affects ablative treatment outcomes. We investigated different durations of AEGs collected during persAF using recurrence quantification analysis (RQA). Methods: 797 bipolar AEGs with different durations (from 0.5 s to 8 s) from 18 patients were investigated. Four RQA-based attributes were evaluated based on AEG durations: determinism (DET); recurrence rate (RR); laminarity (LAM); and diagonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Nine of the 11 most selected features were obtained with RQA or ratios of PCA eigenvalues ( Figure 4 A), probably owing to their sensitivity in detecting changes in the dynamic behavior over time. 47 We observed that AF drivers located in the PVs produced a more regular activity than the extra-PV cases ( Figure 1 A– 1 B.3). In fact, in the simulated episodes, the irregular activity driven by PV cases was limited to a small portion of tissue owing to the presence of anatomical obstacles (eg, the PV sleeves) that prevented the driving mechanisms from meandering to the remaining parts of the atria.…”
Section: Discussionmentioning
confidence: 70%
“…Nine of the 11 most selected features were obtained with RQA or ratios of PCA eigenvalues ( Figure 4 A), probably owing to their sensitivity in detecting changes in the dynamic behavior over time. 47 We observed that AF drivers located in the PVs produced a more regular activity than the extra-PV cases ( Figure 1 A– 1 B.3). In fact, in the simulated episodes, the irregular activity driven by PV cases was limited to a small portion of tissue owing to the presence of anatomical obstacles (eg, the PV sleeves) that prevented the driving mechanisms from meandering to the remaining parts of the atria.…”
Section: Discussionmentioning
confidence: 70%
“…In the past, RQA has been used to analyze the relationship between atrial rate and spectral centre frequency 13 , to quantitatively analyse CFAEs 14 , 15 , to classify atrial electrograms as normal, fractionated or temporally unstable 16 – 18 , and to examine dynamics before and after ablative treatment 19 . This is possible even for short electrogram sequences 17 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, RQA has been extensively used for characterizing the dynamics of heart rate variability [20], [21], cardiac restitution [22], or even combined with machine learning techniques for sudden cardiac death stratification [23] and ECG-based arrhythmia classification [24], [25], among other applications. RQA has been used to specifically characterize the dynamics of intracardiac signals during cardiac disorders [26], [27], [28], [29]. These investigations have shown that RQA-based features represent a promising set of tools to identify phase transitions and discriminate different EP characteristics related to the atrial tissue.…”
Section: Introductionmentioning
confidence: 99%